MiR-20a regulates sensitivity of colorectal cancer cells to NK cells by targeting MICA. Issue 7 (2nd July 2019) - Tang, Siwen; Fu, Hongyu; Xu, Qihua; Zhou, Ying
Abstract : Colorectal cancer (CRC) is one of the leading cancer-related causes of deaths in the world. Recently, microRNAs have been reported to regulate the tumor growth, invasion and the immunosuppression. In the present study, we found that miR-20a was increased in human CRC specimens compared with the healthy normal tissues. However, miR-20a overexpression and knockdown did not impair the CRC cell growth in vitro . Our results indicated that CD107a + NK cells are increased in CRC group. Furthermore, cytotoxicity assays demonstrated that miR-20a knockdown promoted the CRC cells sensitive to NK cells, whereas miR-20a overexpression showed the opposite results. Our results suggest that the regulation of NK cells by miR-20a depends on NKG2D. Luciferase reporter assays revealed that the NKG2D ligand Major Histocompatibility Complex (MHC) class I-related chain genes A (MICA) is the direct target of miR-20a. Flow cytometry showed the MICA protein level is significantly reduced in miR-20a-overexpressing CRC cells and increased in miR-20a knockdown CRC cells. Taken together, our results suggest that miR-20a regulates sensitivity of CRC cells to NK cells by targeting MICA.